Penguatan Etika dan Profesionalisme Guru melalui Game Interaktif Etprof - Alfan, Muhammad; Rosyida, Fatiya; Prestiadi, Dedi; Oktaviani, Herlina Ike; Kusuma, PaundraWangsa Fajar (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The issue of low ethical literacy and teacher professionalism at SMP Negeri 28 Kota Malang served as the foundation for implementing this community service program. Some teachers still perceive teaching merely as an administrative duty rather than a moral calling, and they lack innovation in both instructional practices and the use of technology. This program aims to strengthen teacher ethics and professionalism through the development and training of the interactive game Etprof. The community service activities were carried out using a participatory approach through three stages: socialization, training (workshops), and evaluation using questionnaires. The results indicate that participants showed very positive perceptions of Etprof’s effectiveness in enhancing understanding of teaching ethics, professionalism, and self-reflection. The percentage of “agree” and “strongly agree” responses ranged from 88% to 100% across aspects such as material usefulness, media effectiveness, and training relevance. Etprof was considered effective as it provides realistic ethical simulation scenarios, facilitates reflective thinking, and encourages the integration of technology in teaching practices. Consequently, the use of Etprof strengthens ethical awareness, professional attitudes, and teacher readiness to face educational challenges in the Society 5.0 era. This innovation holds potential for further development and replication as a technology-based community service model in other schools.